2019
DOI: 10.1097/mej.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Are on-scene blood transfusions by a helicopter emergency medical service useful and safe? A multicentre case–control study

Abstract: Neither survival benefits nor a decreased incidence of shock on admission were observed after prehospital helicopter emergency medical service URBC transfusions. There were no prehospital transfusion reactions in this study; therefore, URBC transfusions were deemed to be safe. A prospective randomized study is warranted to evaluate the effect of early URBC transfusions and transfusions with preheated URBC on the survival of patients with severe prehospital haemorrhagic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Studies comparing vital parameters in PHTRBC patients vs non‐receivers report conflicting results: significantly lower occurrence of hypotension, a higher DBP, and a higher BE and pH have been reported in PHTRBC patients, but in contrast, significantly lower SBP, a higher HR, a lower pH and a lower bicarbonate level have also been found. Other studies found no significant differences in either SBP, DBP, HR, BE, lactate, change in mean BP or in HR or occurrence of “shock on admission.” Kim et al compared PHTRBC with PHTRBC + PHT‐plasma and found no significant differences in SBP, HR, lactate, BE or pH. Brown et al measured base deficit and lactate levels on arrival to hospital, and used these to calculate the odds of shock.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Studies comparing vital parameters in PHTRBC patients vs non‐receivers report conflicting results: significantly lower occurrence of hypotension, a higher DBP, and a higher BE and pH have been reported in PHTRBC patients, but in contrast, significantly lower SBP, a higher HR, a lower pH and a lower bicarbonate level have also been found. Other studies found no significant differences in either SBP, DBP, HR, BE, lactate, change in mean BP or in HR or occurrence of “shock on admission.” Kim et al compared PHTRBC with PHTRBC + PHT‐plasma and found no significant differences in SBP, HR, lactate, BE or pH. Brown et al measured base deficit and lactate levels on arrival to hospital, and used these to calculate the odds of shock.…”
Section: Resultsmentioning
confidence: 89%
“…However, in six other studies reporting matched or adjusted data, no significant effect on mortality was found, either at 3 hours, 6 hours, 24 hours, 28 days or 30 days post‐infusion, for in‐hospital mortality or overall mortality (Table ). Conversely, Kim et al found significantly lower mortality at 24 hours and a lower mortality overall for patients transfused with both PHT‐plasma and PHTRBC compared with patients receiving PHTRBC only.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations